Prevalence of depression and anxiety among cancer patients - Nikbakhsh, Novin (Babol University of Medical Sciences, 2014)
Background: Depression and anxiety had negative effects on the quality of life of cancer patients, thus hospital anxiety and depression scale (HADS) is a useful instrument for screening these problems. This research was performed to assess the prevalence of their anxiety and depression. Methods: From 2012-2013, one hundred fifty patients with recent diagnosis of different cancers in Babol, Iran were assessed. A presumptive diagnosis of anxiety and depression was based on a four point 14-item HADS. The score of 0-7 means without clinical symptoms of anxiety or depression, 8-10 mild and 11-21 symptomatic anxiety or depression. The data were collected and analyzed. Results: Forty-four (29.3%) patients had mild anxiety, 25 (16.7%) symptomatic anxiety but mild and symptomatic depression were seen in 40 (26.7%) and 32 (21.3%) patients, respectively. There were significant relationships between anxiety, depression and the age group of the patients with higher frequency in older ages. There were significant relationships between anxiety and depression with the type of cancer and type of treatment. Breast and stomach cancer patients had the highest prevalence of anxiety and depression and the higher prevalence was observed in the patients who received chemotherapy as the single treatment. Conclusion: The results show that patients with breast and stomach cancer had the highest prevalence of anxiety and depression among all others cancer patients.